"Far from the mind": Preliminary evidence of avoidance bias for emotional facial expressions among earthquake victims. (1st June 2021) - Sagliano, Laura; Conson, Massimiliano; Saporito, Gennaro; Carolei, Antonio; Sacco, Simona; Pistoia, Francesca
Abstract: Facial expressions are important threat cues that can induce attentional biases, particularly among anxious individuals, facilitating precautionary behaviour. However, no study has assessed earthquake victims for attentional bias related to emotional facial expressions. In this study, we set out to bridge this gap by testing biases for emotional facial expressions in relation to psychopathological symptoms in a group of victims of the 2009 L'Aquila (Italy) earthquake. In a between-subjects design, 14 earthquake victims and 14 controls completed an exogenous cueing task to assess attentional biases in respect of seven facial expressions (happy, sad, angry, disgust, surprise, fearful and neutral). In each trial, one face was briefly presented on the right or left side of the screen as a cue and was followed by a target (a small dot). Participants had to indicate the position of the target shown on the same side as the emotional face (valid trials) or the opposite side (invalid trials). MANOVA performed on the engagement and disengagement scores demonstrated that earthquake victims and controls differed only in the engagement scores for fearful expression. Moreover, single-sample t-tests demonstrated that victims showed attentional avoidance of both fearful and happy expressions. Finally, in earthquake victims, avoidance of fearful expressions negatively correlated with anxiety-related cognitive concerns. Although the results are preliminary, we provide evidence of attentional avoidance of emotional faces among earthquake victims that is present years after the traumatic event. Cognitive mechanisms underlying such a bias and their implications are discussed.